Traffic noise: More than just mere annoyance? - Quraishy, Maryam Saida; Dar, Arifa; Narejo, Savera (Journal of the Pakistan Medical Association, 2023)
Madam, As industrialisation and technology become more global, quality of life is far better than years before. One such development is better transportation. With the advent of cars and buses, transport is easier than ever and is an integral part of almost everyone’s daily life. However, with any fast-paced change, novel situations bring along problems. Along with convenience, increased traffic brings along its own issues, one of which is the increase in environmental noise. Continue...